Central bank intervention and exchange rate volatility in the inflation-targeting regime - Haryo Kuncoro; Caroline Geetha; Fafurida Fafurida (IDEAS, 2024)
This paper examines the impact of central bank intervention on the exchange rate fluctuations within the framework of inflation-targeting. Focusing on Indonesia, the Philippines, and Thailand from 2005(7) to 2022(12), empirical analysis using quantile regression demonstrates that the central bank intervention mitigates real exchange rate volatility. However, there is a discernible upward linear trend in the coefficient related to market intervention. While overall behavior tends to be symmetrical, selling intervention and interventions during depreciation periods differently affect real exchange rate volatility across quantiles. Those results underline the importance for monetary authorities to consider shifts in exchange rate expectations over the medium term. Accordingly, the selective implementation of market intervention, tailored to the dynamics of real exchange rate volatility, is essential for upholding the credibility of inflation-targeting monetary policy.